Type VI secretion system helps find a niche - Kapitein, Nicole; Mogk, Axel (Cell host and microbe, 2014)
Type VI secretion systems (T6SSs) deliver toxins into target cells and thus play a role in bacterial warfare. In this issue of Cell Host & Microbe, Ma et al. (2014) demonstrate that T6SS-dependent attack during interbacterial competition in the host context enables niche colonization by Agrobacterium tumefaciens.
Gesehen am 06.08.2020